El Príncipe : de la fiction d’une série à la réalité d’un quartier - Alicia Fernández García (Cahiers de Civilisation Espagnole Contemporaine)
This contribution is interested with the image that the serie El Príncipe gives of the city of Ceuta, a Spanish enclave in Morocco, which is ravaged by unemployment, inequalities and the size of the informal economy, in addition with the scourge of jihadism since a few years. In spite of the presence of a few stereotypes and of simplified images, this fiction had nevertheless the merit to give a media spotlight on a city generally forgotten by the Spaniards. It has also put on the front of the stage some social issues which its inhabitants are facing.